Global crisis management and higher education : - Oleksiyenko, Anatoly; Mendoza, Pilar; Cárdenas Riaño, Fredy Esteban; Dwivedi, Om Prakash; Kabir, H. Arif; Kuzhabekova, Aliya; Muweesi, Charles; Vutha, Ros; Shchepetylnykova, Ielyzaveta (John Wiley & Sons Ltd., 2022)
Campus crisis management remains an understudied topic in the context of COVID -affected higher education. In this paper, we contrasted the ability to tame the wicked problems brought by the pandemic of COVID-19 in private and public universities in Bangladesh, Cambodia, Colombia, India, Kazakhstan, Uganda, and Ukraine. The cross-country analysis and diversity of institutional types allowed us to consider a wide range of challenges faced by academic leaders and their institutions during the global pandemic. By drawing on institutional policy reviews and interviews with university administrators, we have examined tensions between the human and institutional agencies on these crisis-stricken campuses given differing institutional coupling, sizes, resources, and missions. The focus on agential co-dependencies and institutional coupling lays the ground for conceptualizing campus crisis management as a culturally specific construct in the context of higher education affected by the global pandemic. KEYWORDS COVID-19, crisis management, global higher education, human agency, institutional agency
agency and coupling in the context of wicked COVID-19 problems.
Article